PENGARUH DISIPLIN KERJA DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN PADA PT POLYMINDO PERMATA TANGERANG - Khaila Fadlya Maharani; Feb Amni Hayati (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Abstract. The purpose of this study is to determine the influence of Work Discipline and Job Satisfaction on Employee Performance at PT. Polymindo Permata Tangerang, both partially and simultaneously. The research method used is a quantitative method. The population in this study were all employees of PT. Polymindo Permata Tangerang, totaling 62 respondents with a sample of 62 respondents. Data analysis techniques used data instrument tests, classical assumption tests, linear regression tests, correlation coefficient tests, determination coefficient tests, and hypothesis tests. The results showed that Work Discipline had a significant effect on Employee Performance with the regression equation Y = 10.606 + 0.741X1. The correlation coefficient value was 0.750, the determination coefficient had a contribution of 56.3%, and the hypothesis test obtained a t count value > ttable or (8.799 > 2.001) which means H01 was rejected and Ha1 was accepted. Job Satisfaction significantly influences Employee Performance with the regression equation Y = 6.838 + 0.886X2, a correlation coefficient of 0.854, a coefficient of determination contributing 72.9%, and the hypothesis test obtained a calculated t value > t table or (12.690 > 2.001), meaning H02 is rejected and Ha2 is accepted. Work Discipline and Job Satisfaction significantly influence Employee Performance with the regression equation Y = = 2.212 + 0.323X1 + 0.660X2. The correlation coefficient of 0.888, a coefficient of determination contributing 78.8%, and the hypothesis test obtained a calculated F value > F table or (109.657 > 3.150), meaning H03 is rejected and Ha3 is accepted. Keywords: Work Discipline, Job Satisfaction, Employee Performance